Impact of directors' quality on earnings quality : a study on SGX listed companies. - Lau, Sarah Sheng Ai. (2008)
An empirical research on the relationship between earnings quality and directors' quality. The study aims to find out the impact of directors' competence and commitment on the informativeness on earnings using tested statistical models.